Entomopathogenic fungus Clonostachys rosea as a biocontrol agent against whitefly (Bemisia tabaci). Issue 8 (3rd August 2018) - Anwar, Waheed; Ali, Sajid; Nawaz, Kiran; Iftikhar, Sehrish; Javed, Muhammad Asim; Hashem, Abeer; Alqarawi, Abdulaziz A.; Abd_Allah, Elsayed Fathi; Akhter, Adnan
ABSTRACT: Whitefly ( Bemisia tabaci ) is a notorious insect pest of many economic important crop plants including cotton, tomato, etc. The main objective of the study was to evaluate the efficacy of new biological control agent to replace toxic chemical pesticides from agro-ecosystem. Clonostachys rosea associated with whitefly and aphid ( Aphis gossypii ) on cotton plants was isolated and characterised on a morphological and molecular basis. Phylogenetic analysis was also performed based on the internal transcribed spacer (ITS) region. Pathogenicity of C. rosea was evaluated in two concentrations against fourth instar nymphal and adult stages of B. tabaci. The study revealed that C. rosea was highly parasitic against fourth instar nymphs than adults at different spore concentrations. Two isolates of C. rosea were identified in this study, and both were morphologically similar. However, differences were observed in the ITS region of the C. rosea isolates. Our results showed that C. rosea has the prospects to serve as a potential biocontrol agent against economically important insect pests.